Compositeness effects in the anomalous weak-magnetic moment of leptons - GonzalezGarcia, M. C.; Novaes, Sérgio Ferraz [UNESP] (Elsevier B.V., 1996)
We investigate the effects induced by excited leptons, at the one-loop level, in the anomalous magnetic and weak-magnetic form factors of the leptons. In particular, we compute their contributions to the weak-magnetic moment of the tau lepton, which can be measured on the Z peak, and we compare it with the contributions to g(mu) - 2, measured at low energies.